Factors Affecting the Competitiveness of Automotives Parts Manufacturers in Lean Production for Productivity - พันธุ์ธนากุล, พลเทพ (The Journal of Development Administration Research, 2015)
The object of this research was to study the factors affecting the competitiveness of automotives parts manufacturers in lean production for productivity. Use quantitative research methods. The research sample was automotives parts manufacturers in Bangkok, Central and Eastern Region, 288 companies analyzed data using structural modeling equation analysis with PLS-Graph program. The result made a conclusion that overall product maintenance and quality control has a direct effect on lean production. While accessibility features such as location and technology are also part of this. Lean manufacturing affects productivity, delivering quality, cost, and cost. This results in a competitive market share. Consequently, lean training should be provided, and development should be broad, right and continuous. It also facilitates the supply of lean manufacturing equipment. To make the automotive parts industry, which has a lot of human resources involved, has been developed and elevated.